Title not available in English. - Sydenstricker, John M. (1991)
Mobility of migrants: Autonomy or subordination in the Amazon region? This article focuses the mobility of the population settled in a Rural area of the State of Rondônia: the Machadinho Settlement Project. The monthly mobility is examined during a period of 24 months (July/85 to June/87) through an average permanency index. Mobility is analyzed according to general demographic variables as sex, age and migratory experience. In spite of the relatively low levels of mobility, the differentials that a rise reflect the conditions under which the occupation of Machadinho occurred and the seasonality of the regional agricultural cycle. Mobility pattern are examined in relation to the most recent debates on the "peasantry" in Brazil and on the frontier. The existence of different strategies or distinctive projects within the same population is discussed, establishing a type of dynamic interaction between autonomy and subordination.